ON THE BIOLOGY OF THE PENAEID PARAPENAEOPSIS SCULPTILIS (HELLER) IN THE BOMBAY AREA - Sukumaran, K K; Rajan, K N (Indian Journal of Fisheries, 2011)
Male and female Paiapenaeopsis sculptilis in the fishery registered monthly average growths of 5.88 mm and 8.17 mm, respectively. The young prawns recorded faster rate of growth, about 15 mm per month. In the inshore fishery the smallest female with fully matured ovary measured 88 mm in length, whereas in the Arnala creek the prawns measuring 71 mm and above were found to be mature. Spawning is year-round with two peaks, one during February-March and another during July-November. The chi-square values at 5% probability level showed that the observed proportion of males in difi’erent months of the years except 1969 were statistically significant. Sizewise distribution of sex ratio revealed that males were predominant in the sizes within 78-98 mm and females outnumbered males in the rest of the sizes.